The status of 25‐hydroxyvitamin D across the spectrum of glucose tolerance among middle‐aged and elderly Chinese individuals. (9th September 2014) - Guan, Conghui; Zhen, Donghu; Tang, Xulei; Yang, Xiaomei; Zhu, Tengfei; Fu, Songbo; Tian, Yunling
Summary Context Although vitamin D status and its inverse association with diabetes among White people have been recognized, little research on vitamin D status has been well conducted in Chinese individuals based on glucose tolerance. Objective To compare the vitamin D status of Chinese individuals aged 40–75 years based on the glucose tolerance status. Design and methods Serum 25OHD was measured in a cross‐sectional sample of 10 038 individuals aged 40–75 years from Lanzhou city, which is located in western China. Results People with normal glucose tolerance (NGT, n = 4744), prediabetes (n = 2808) or diabetes (n = 2486) aged 40–75 years were included in the study. The difference in 25OHD concentration between people with NGT and prediabetes was not significant (16·5 vs 16·0 ng/ml, P = 0·773), but the 25OHD concentration of diabetes was higher than that of subjects with NGT (16·5 vs 16·5 ng/ml, P = 0·025) and prediabetes (16·5 vs 16·0 ng/ml, P = 0·032) after adjusting confounders. There was no difference in the prevalence of vitamin D deficiency between people with NGT and diabetes (74·7% vs 74·0%, P = 0·535), but the prevalence of vitamin D deficiency of prediabetes was higher than that of people with NGT (77·0% vs 74·7%, P = 0·024) and diabetes (77·0% vs 74·0%, P = 0·012). Conclusions Although vitamin D status was significantly different across the spectrum of glucose tolerance in middle‐aged and elderly Chinese individuals, the difference was not clinically significant. The results, however, highlight the very high prevalence of vitamin D deficiency in this population and should raise the awareness of this important public health issue among health‐care providers.